Species composition of birds in converted coastal area of Barru Regency, South Sulawesi, Indonesia. Issue 1 (May 2021) - Priosambodo, D; Nadiarti, N; Nafie, YA La; Jamal, M
Abstract: Sulawesi, the largest island in Wallacea region is well-known for its avifauna diversity and endemism. The island is mountainous and surrounded by long coastline with mangrove and wetland ecosystems. To date, most of coastal area converted into fishpond, rice field and settlement. As a result, many species are seriously threatened by land conversion. Nevertheless, species composition of birds in the converted coastal area has poorly studied. To fill in the information gaps, we conducted research in Universitas Hasanuddin fishpond. The fishpond situated in Tanjung Kupa, a small peninsula in Mallusetasi subdistrict, Barru regency, South Sulawesi. This research aimed to figure out the species composition, ecological niche, conservation status and feeding guild of the bird at converted coastal area. Data were collected using MacKinnon list method in the morning at 06.30-09.30 and in the afternoon at 15.30-17.30 from August to September 2020. From the observations, we recorded 37 bird species from 25 families consist of 29 resident, 4 migratory, 3 introduce and 1 endemic species. Most of common birds species dominated by open-country specialist which indicates a change in the composition of bird species in the converted coastal areas of Barru Regency.